DEVELOPMENT OF A METHOD FOR FUNCTIONING OF DECENTRALIZED COMPUTER SYSTEMS IN SOLVING THE PROBLEM OF INHERITANCE - ONATSKYI, VITALII; SAVINOV, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This article explores the application of smart contracts in inheritance matters within the contemporary digital realm. The first part analyzes the complexities and traditional processes of inheritance in Ukraine, identifying various forms of inheritance based on testamentary and intestate succession laws. The subsequent sections highlight the advantages of utilizing smart contracts, emphasizing transparency, automation, and cost-effectiveness in managing inheritance. Additionally, the article discusses legal considerations and underscores the importance of ensuring the reliability of smart contracts. Overall, smart contracts represent an innovative approach to managing inheritance, offering new opportunities for efficient, transparent, and trustworthy asset distribution among heirs in decentralized systems. For the first time, the use of a smart contract in the blockchain was proposed to solve the problem of succession, which opens the way to new opportunities in the field of inheritance and management of inherited assets. They provide transparency, automation, and cost-effectiveness, making them an attractive tool for continuity in decentralized computing systems. Therefore, smart contracts represent an innovative approach to the management of inherited property, which creates new opportunities for efficient, transparent and trustful distribution of property between heirs. In addition, they can ensure the security and inviolability of the rights of the heirs, since all the terms of the inheritance distribution are fixed in the code of the contract, which cannot be changed, which excludes the possibility of its manipulation by any party. Thanks to blockchain technology, smart contracts can also provide security and necessary documentation to enforce inheritance rights to property, while avoiding the shortcomings of traditional inheritance management systems.
Keywords: distributed system; decentralized systems; blockchain